Prenatal Yoga bagi Ibu Hamil Risiko Tinggi - Monica Kartini (Jurnal Pengabdian Serulingmas, 2023)
Background: High risk pregnancy (HRP) is a pregnancy where the pregnant mother and fetus are at higher risk of illness or death during pregnancy, labor and after delivery. One of the efforts that can be made to prevent complications due to high-risk pregnancies is to do prenatal yoga. This community service program is aimed to improve comfort level of the women with HRP through prenatal yoga. Methods: The community service activity begins with the preparation stage, followed by implementation of prenatal yoga, and evaluation. The implementation of prenatal yoga was carried out for 60 minutes accompanied by instrumental music and was attended by 7 pregnant women in the second and third trimesters. Results: During prenatal yoga practice sessions, the participants can follow the yoga postures of the instructor. After practicing yoga, the mothers said that they felt more comfortable and relax. Conclusion: Prenatal yoga improves the pregnant women’s comfort and is safe to do for high-risk pregnant women. Continuous program is needed to facilitate pregnant women to attend prenatal yoga classes regularly. Also, further research is needed to study the effects of prenatal yoga in high-risk pregnancies.